Seismicity in Costa Rica during 2015 - Porras, Juan L. (2016)
During 2015, the National Seismological Network (RSN: UCR-ICE) located 6989 earthquakes and reported 168 felt events. There were 13 significant earthquakes with magnitude Mw > 5.0. The majority (86%) of felt earthquakes were shallow (< 30 km) and 81% had magnitudes (Mw) between 3.0 and 4.9. Local and regional faulting caused 61% of the felt earthquakes and the subduction of the Cocos Plate caused 37%. The geographic areas with the highest seismicity during 2015 were the Guanacaste and Central volcanic cordilleras, Los Santos region, and an area offshore the Nicoya peninsula. The highest intensity observed in Costa Rica during 2015 was V+ (Modified Mercalli).